(untitled) (South Asian Journal of Agriculture, 2019)
Betel leaf is a traditional cash crop in Bangladesh. Betel leaf cultivation is such like traditional agro-based occupation. This cash crop is locally known as pan and it’s scientific name is Piper betel that is the leaf of a vine belonging to the Piperaceae family. This study makes a modest attempt to know the livelihood pattern of betel leaf cultivators of south-west region of Bangladesh. The data were collected from Maskata Village in Betaga Union and Piljanga Village in Piljanga Union under Fakirhat Upazila in Bagerhat District, Bangladesh. This study was descriptive in nature. The paper is based upon qualitative approach which includes analysis of existing secondary sources of data. It also deals with primary data collected through Case Studies, Focus Group Discussions (FGDs), Key Informants Interview (KII) methods. The data were analyzed into five categories including: natural capital, financial capital, social capital, physical capital and human capital. Betel leaf cultivation is an ancestral occupation of the respondents. Most of the family structure is nuclear and have strong bonding within community. Poor socio-economic conditions include lack of sanitation, unavailability of pure drinking water and lack of health care center creates pressure on their health status. On the contrary, low education, poor savings and poor credit facilities with high rates of bank interest makes them more vulnerable. Water logging and rot diseases are other challenges of this cultivation. The children who are involved in tertiary education, they mostly not come back their ancestral occupation. From the study it is revealed that, integrated as well as comprehensive intervention program with social awareness and safety net program should be run by the Government and NGOs for the betterment of this vulnerable occupation. Moreover, health worker should provide medicine and other health incentives for physically vulnerable groups. This paper would contribute to the policy making and taking necessary initiatives especially for this occupational groups. South Asian J. Agric., 7(1&2): 34-37